2011
DOI: 10.1294/jes.22.21
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Formation after Intensive Exercise in Thoroughbred Skeletal Muscles

Abstract: Although high oxygen consumption in skeletal muscle may result in severe oxidative stress, there are no direct studies that have documented free radical production in horse muscles after intensive exercise. To find a new parameter indicating the muscle adaptation state for the training of Thoroughbred horses, we examined free radical formation in the muscle by using electron paramagnetic resonance (EPR). Ten male Thoroughbred horses received conventional training for 18 weeks. Before and after the training per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Studies have shown that exercise promotes oxidative stress in the body 5 , and that high-intensity exercise, both long and short, can lead to increased free radical production in active skeletal muscles, resulting in the formation of oxidized lipids and proteins in the working muscles [6][7][8] . This uncontrolled production of reactive oxygen species (ROS) can damage cells.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that exercise promotes oxidative stress in the body 5 , and that high-intensity exercise, both long and short, can lead to increased free radical production in active skeletal muscles, resulting in the formation of oxidized lipids and proteins in the working muscles [6][7][8] . This uncontrolled production of reactive oxygen species (ROS) can damage cells.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen consumption during exercise could increase up to 7 folds in equine [7]. Free radical spikes in exercise have been demonstrated [8]. However, conflicting results are there.…”
Section: Introductionmentioning
confidence: 99%